2023
DOI: 10.1002/ar.25336
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the morphology of adult tibia and fibula from Sima de los Huesos site in sierra de Atapuerca, Burgos, Spain

Laura Rodríguez,
Rebeca García‐González,
Juan Luis Arsuaga
et al.

Abstract: The analysis of the locomotor anatomy of Late Pleistocene Homo has largely focused on changes in proximal femur and pelvic morphologies, with much attention centered on the emergence of modern humans. Although much of the focus has been on changes in the proximal femur, some research has also been conducted on tibiae and, to a lesser extent, fibulae. With this in mind, we present one of the largest samples of the same population of human tibiae and fibulae from the Middle Pleistocene to determine their main ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 89 publications
(186 reference statements)
0
0
0
Order By: Relevance
“…The study of tarsals carried out here also found similar traits in SH relative to Neandertals that differentiate both populations from recent H. sapiens. This confirms the evolutionary relationship between these two paleodemes as evolutionary sister groups as previously established by other anatomical regions (Arsuaga et al, 2014(Arsuaga et al, , 2015Rodríguez et al, 2024a). This similarity in postcranial anatomical traits between SH and Neandertals is likely related to a high degree of biomechanical stress, and to the greater general robustness of the postcranial skeleton.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The study of tarsals carried out here also found similar traits in SH relative to Neandertals that differentiate both populations from recent H. sapiens. This confirms the evolutionary relationship between these two paleodemes as evolutionary sister groups as previously established by other anatomical regions (Arsuaga et al, 2014(Arsuaga et al, , 2015Rodríguez et al, 2024a). This similarity in postcranial anatomical traits between SH and Neandertals is likely related to a high degree of biomechanical stress, and to the greater general robustness of the postcranial skeleton.…”
Section: Discussionsupporting
confidence: 84%
“…The studies of the postcranial skeleton of the SH hominins have allowed to establish some traits similar among this Middle Pleistocene population and Neandertals (Arsuaga et al, 2015;Carretero et al, 1997;García-Gonz alez et al, 2024;Pablos et al, 2017;Rodríguez et al, 2024a). The study of tarsals carried out here also found similar traits in SH relative to Neandertals that differentiate both populations from recent H. sapiens.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Without a doubt, the SH population exhibits high robusticity in the postcranial skeleton in general (Arsuaga et al, 1999(Arsuaga et al, , 2015G omez-Olivencia et al, 2007;Bonmatí et al, 2010;Pablos et al, 2017;Carretero et al, 201., 2024a;García-Gonz alez et al, 2024;Rodríguez et al, 2024a), and in the metatarsal and pedal phalanges in particular. This concurs with the previously proposed large corporal size for the SH population and its primitive biotype (Arsuaga, 2010;Carretero et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This likely denotes the high robusticity of this Middle Pleistocene population, that is, for the same stature, the bodies are broader than current and fossil modern humans. This "wide Homo" bauplan consisting of a large thorax with broad shoulders and pelvises, and great musculature and body mass probably derives from earlier populations such as Homo ergaster/antecessor from which Homo sapiens departed (Arsuaga, 2010;Arsuaga et al, 2015;Carretero et al, 1999Carretero et al, , 2004Carretero, Rodríguez, et al, 2024b;García-Gonz alez et al, 2009;Lorenzo et al, 2015;Pablos et al, 2012;Rodríguez et al, 2024a).…”
Section: Foot 1 and Foot 2 Associationmentioning
confidence: 99%